The Economic Impact and Strategic Significance of the Semiconductor Industry in Malaysia: Penelitian - Nur Aifiah Binti Ibrahim (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Semiconductors are a critical foundation of modern life and economic development in Malaysia, enabling the functioning of digital devices, communication systems, and healthcare technologies. As Malaysia progresses toward a technology-driven and high-income economy, reliance on semiconductor-based systems has increased across daily activities and manufacturing. The country plays an important role in the global semiconductor supply chain, particularly in electrical and electronics manufacturing, assembly, and testing, which contributes significantly to employment, exports, and foreign investment. However, their widespread use, awareness of the importance of semiconductors among Malaysians remain limited due to their largely invisible role in end products. This study examines the significance of semiconductors in Malaysian life and the economy while assessing public understanding to support technological preparedness, innovation, and sustainable national development.